Pengaruh Penggunaan Bungkil Kelapa yang Difermentasi dengan Ragi Tape dalam Ransum Terhadap Bobot Karkas Ayam Broiler Jantan - Filawati, Filawati (Fakultas Peternakan Universitas Jambi, 2008)
The experiment was conducted to determine the effect of using fermented coconut cake with tape yeast on dry metter intake, slaughtered weidht, carcass weight and carcass percentage. A hundred two days old male chicken was used in thiss study. This study was assigned into completely randamized design with 5 treatment and 4 replications.Â The tretment was using 100% commercial feed, using 10% and 20% of coconut cake in commercial feed and using 10% and 20% of fermented coconut cake with tape yeast in commercial feed. Parameters measured dry matter intake, slaughtered weight, carcassweight and carcass persentage. It concluded that coconut cake and permented coconut cake with tape yeast can be mixed into the ration up to 20% to subtitute commercial feed.